2016
DOI: 10.3892/ol.2016.4745
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal carcinomatosis as the primary presentation of relapse in breast cancer

Abstract: Abstract. Leptomeningeal metastasis (LM) is an uncommon presentation of relapse in breast cancer, which is associated with poor clinical outcomes and poor prognosis. Notably, LM most commonly occurs in breast cancer. The aim of the present review was to investigate the occurrence of LM as the primary presentation of relapse following remission in breast cancer patients and to determine whether specific histological subtypes are predisposed to meningeal metastases. In addition, the present review evaluated whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…LMD occurs in ≤5% of breast cancer patients. It usually occurs at the advanced stage of the disease and may occur as the first presentation of metastasis in 9-15% of patients diagnosed with breast cancer [ 3 ]. Rarely, patients can present with LMD at diagnosis without previously known breast cancer as in our case [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMD occurs in ≤5% of breast cancer patients. It usually occurs at the advanced stage of the disease and may occur as the first presentation of metastasis in 9-15% of patients diagnosed with breast cancer [ 3 ]. Rarely, patients can present with LMD at diagnosis without previously known breast cancer as in our case [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment modalities recommended for breast cancer patients with LMD are intrathecal chemotherapy, radiation therapy to the affected area, and approaches to decrease the intracranial pressure [ 3 ]. Treatment involves multidisciplinary care with symptom management and pain control, and therapies are given with palliative intent.…”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestations of spinal cord involvement are fatigue, pee and stool dysfunction, limb paresthesia, neck or back radiculopathy and pain. Neck stiffness is present in less than 15% of MC patients [7,14,15] . Others can also show the in ammatory response of NM.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time of patients diagnosed with MC is 4.27 months (0.11-3.78), and 23% of patients have a survival time of more than 1 year after diagnosis of MC. Related studies have shown that invasive ductal carcinoma is prone to parenchymal brain metastasis, while invasive lobular carcinoma is prone to meningeal metastasis [15] . Autopsy data from patients with metastatic breast cancer show that the incidence of MC in invasive lobular breast cancer is about 14%, while that in invasive ductal breast cancer is 1% [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Of all the subtypes, Human epidermal growth factor receptor 2 (HER2)-positive BC has a predilection for brain metastasis but is less likely to develop LM at the same time (7). Previous studies have reported that the frequency of HER2-positive BC among LM patients ranges between 14%-29% (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%